2017
DOI: 10.1155/2017/9650420
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Etch-and-Rinse, Self-Etch, and Universal Dental Adhesive Systems in Fibroblast Cell Line 3T3

Abstract: The aim of this study was to evaluate in fibroblast cultures the direct cytotoxic effects of etch-and-rinse, self-etch, and universal adhesive systems. The sterile glass cover slips (n = 3) were then immersed in culture medium to obtain the eluates for the experimental groups: (1) Adper™ Single Bond 2; (2) Ambar; (3) Adper™ Scotchbond™ Multi-Purpose; (4) Scotchbond™ Universal; (5) Ambar Universal; and (6) OptiBond All-In-One. As a negative control, sterile glass cover slips were immersed in culture medium only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Present study was designed to compare the results of total etch technique with selected etch technique using USPHS criteria. The USPHS criteria was used as it is found to be a reliable method for assessment of various parameters of restorations such as margins integrity, discoloration of margins, caries, post-op sensitivity and shade selection [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present study was designed to compare the results of total etch technique with selected etch technique using USPHS criteria. The USPHS criteria was used as it is found to be a reliable method for assessment of various parameters of restorations such as margins integrity, discoloration of margins, caries, post-op sensitivity and shade selection [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that selected etch method produced higher bond strength which is good for good margins of restorations and proper seal of it therefore it is recommended that enamel cavo-surface margins should be etched too before application of self etching method 18 . It is recommended that dentine cavo-surface margins should not be etched before application of self etching method 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many researchers studying the cytotoxicity of different generations of dental adhesives 8,16,[62][63][64][65] , studies on the cytotoxicity of universal adhesives are even limited 66,67) . In addition to that, despite the above-mentioned studies, to the authors knowledge, there are no studies that have evaluated the cytotoxicity of universal adhesives using real-time and continuous analysis of cell vitality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, despite the above-mentioned studies, to the authors knowledge, there are no studies that have evaluated the cytotoxicity of universal adhesives using real-time and continuous analysis of cell vitality. A study investigated cytotoxic effects of universal [ 67) , however, the authors have not provided information about the duration of exposure of the extracts to the cells. The authors concluded that all tested adhesive systems except universal adhesives, reduced cell viability between 26.04 and 56.57%.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Several research mention that the free monomers of dentine bonding materials are suspected of being one cause of postoperative pain and of teeth getting progressively necrotized. [21] Pupo et al [22] analyzed the metabolic effects of several adhesive materials and revealed that the toxicity of the current adhesive systems varied, they suspected that it was likely related to the level of residual monomers. These free monomers have also been considered capable of damaging fibroblast cells in dentine and pulp tissue.…”
Section: Discussionmentioning
confidence: 99%